The Effects of Successful Percutaneous Mitral Balloon Valvuloplasty on Acute and Intermediate Term Aortic Stiffness. Issue 5 (27th October 2014) - Inci, Sinan; Nar, Gökay; Erol, Mustafa Kemal; Demirelli, Selami; Duman, Hakan; Serdar, Serkan; Erol, Fatih
Abstract : Aim: The aim of this study was to evaluate the effects of percutaneous mitral balloon valvuloplasty (PMBV) on short‐ and intermediate‐term aortic stiffness in patients with mitral stenosis. Materials and Methods: This prospective study included 56 patients with critical mitral stenosis in normal sinus rhythm (68% female; mean age: 42 ± 11 years) and 37 healthy controls. Aortic stiffness was measured using transthoracic echocardiography before PMBV, and 24–48 hours and 1 year post procedure. Results: Aortic strain and distensibility were significantly higher in the patients with mitral stenosis, both after PMBV and 1 year post procedure, whereas the aortic stiffness index (ASI) was significantly lower. There was also a significant decrease in mitral mean gradient (MMG) and systolic pulmonary artery pressure (sPAP) after PMBV, based on echocardiography and catheterization. Mitral valve area (MVA) significantly increased after PMBV. There was a significant correlation between change in ∆MVA and ∆MMG and aortic elastic properties. There was a significantly negative correlation between the ∆MVA and ∆∆ aortic stiffness (r = −0.62, P < 0.001), and a significantly positive correlation between ∆MMG and ∆ASI (r = 0.60, P < 0.001). Conclusion: Mitral valve stenosis was associated with impaired aortic stiffness and following PMBV, aortic stiffness decreased during both the acute period and the intermediate period.